Treatment of relapsed or refractory Waldenström's macroglobulinemia with bortezomib - Dimopoulos, M.A.; Anagnostopoulos, A.; Kyrtsonis, M.C.; Castritis, E.; Bitsaktsis, A.; Pangalis, G.A. (Haematologica, 2005)
Background and Objectives. Bortezomib is a selective proteasome inhibitor which has shown significant activity in a variety of hematologic malignancies including multiple myeloma, mantle cell lymphoma and marginal zone lymphoma. Thus, this agent is worth studying in patients with Waldenström's macroglobulinemia (WM). Design and Methods. Patients with refractory or relapsed WM were treated with bortezomib administered intravenously at a dose of 1.3 mg/m2 on days 1, 4, 8 and 11 in a 21-day cycle for a total of four cycles. Results. Ten previously treated patients with WM were treated with bortezomib. Most patients had been exposed to all active agents for WM and eight patients had received three or more regimens. Six of these patients achieved a partial response which occurred at a median of 1 month. The median time to progression in the responding patients is expected to exceed 11 months. Bortezomib was relatively well tolerated. The more common toxicities were mild or moderate thrombocytopenia, fever and fatigue while peripheral neuropathy occurred in three patients and one patient developed severe paralytic ileus. Interpretation and Conclusions. Our preliminary data indicate that bortezomib is an active agent in patients with heavily pretreated relapsed/refractory WM. Four cycles of this agent may be adequate to assess sensitivity in this disease. Further studies are needed to confirm our results and to evaluate combinations of bortezomib with other active agents. ©2005 Ferrata Storti Foundation.
Keywords: bortezomib; proteasome inhibitor; Waldenström's macroglobulinemia